2017
DOI: 10.1111/jhn.12474
|View full text |Cite
|
Sign up to set email alerts
|

Algal supplementation of vegetarian eating patterns improves plasma and serum docosahexaenoic acid concentrations and omega‐3 indices: a systematic literature review

Abstract: Background Vegetarians are likely to have lower intakes of preformed docosahexaenoic acid (DHA) than omnivorous populations who consume fish and animal products. As such, vegetarian populations have omega‐3 indices up to 60% lower than those who consume marine products. Algae, the primary producer of DHA in the marine food chain, offer an alternative source of DHA for those who do not consume marine or animal products. This systematic review aims to examine the evidence for the relationship between supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…Aquaculture, or fish farming, offers an alternative, although this practice has been associated with damage and contamination of ecological areas [ 15 ]. For this reason, oil from marine algae has been proposed as an alternative and more sustainable source of ω-3 PUFA [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture, or fish farming, offers an alternative, although this practice has been associated with damage and contamination of ecological areas [ 15 ]. For this reason, oil from marine algae has been proposed as an alternative and more sustainable source of ω-3 PUFA [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common sources of high DHA oils include certain species of fish (e.g. salmon, tuna, sardines) and/or algae [44][45][46]. In Western cultures, dietary DHA levels are generally very low and dietary supplementation for pregnant and lactating women and infants is highly recommended [14,16,47].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported improved recovery with reduced muscle soreness following DHA/EPA supplementation in untrained athletes, although this is following eccentric exercise (Tartibian et al 2009; 2011; Jouris et al 2011). Interestingly, lowered intakes of preformed DHA and EPA are consumed in vegetarian‐based eating patterns with lower omega‐3 indexes observed in these groups compared to omnivorous populations who consume fish and animal products (Craddock et al 2017). The lowered omega‐3 index observed in these groups, including those following a WFPB diet, may negatively influence exercise‐induced stress markers if the athlete fails to consume adequate preformed long‐chain omega‐3 fatty acids in algal forms (DHA/EPA), consume insufficient alpha linoleic acid which can be converted to DHA and EPA or balance consumption of omega‐6 to omega‐3 fatty acids (ideally ~3:1, respectively, for optimal conversion) (Welch et al 2010).…”
Section: Effects Of Plant‐based Dietary Patterns On Immune Status Inmentioning
confidence: 99%